Multicenter phase 2 trial of nintedanib in advanced nonpancreatic neuroendocrine tumors. Issue 16 (11th June 2020) - Iyer, Renuka V.; Konda, Bhavana; Fountzilas, Christos; Mukherjee, Sarbajit; Owen, Dwight; Attwood, Kristopher; Wang, Chong; Maguire, Orla; Minderman, Hans; Suffren, Sheryl‐Ann; Hicks, Karen; Wilton, John; et al.
Abstract : Background: Antiangiogenic‐targeting agents have low response rates in patients with nonpancreatic neuroendocrine tumors (NETs). Nintedanib is an oral antiangiogenic agent that has inhibitory effects on the fibroblast growth factor receptor, which is highly expressed in NETs. The authors hypothesized that nintedanib would be active in patients with nonpancreatic NETs. Methods: Patients with advanced, grade 1 or 2, nonpancreatic NETs who were receiving a stable dose of somatostatin analogue were enrolled. Nintedanib was administered at a dose of 200 mg twice daily in 28‐day cycles. The primary endpoint was progression‐free survival (PFS) at 16 weeks. Results: Thirty‐two patients were enrolled, and 30 were evaluable for the primary outcome. Most had radiographic disease progression within 12 months before enrollment. The 16‐week PFS rate was 83%, and the median PFS and overall survival were 11.0 months and 32.7 months, respectively. Nintedanib was well tolerated and delayed deterioration in quality of life. The baseline serotonin level had a strong, positive correlation with activated but exhausted T cells. Conclusions: Nintedanib is active in nonpancreatic NETs. The immunosuppressive effect of serotonin should be targeted in future clinical trials. Abstract : Angiogenesis and fibroblast proliferation are important disease drivers in nonpancreatic neuroendocrine tumors. Nintedanib, an inhibitor of fibroblast growth factor receptor and vascular endothelial growth factor receptor, has activity in nonpancreatic neuroendocrine tumors, and baseline serotonin, which is known to drive fibroblast proliferation through fibroblast growth factor receptor, has a strong, positive correlation with activated but exhausted T cells.